NATIONALISMS IN MOLDOVA - I. E. Kochedykov (Сравнительная политика, 2015)
The article discusses the various types of nationalism in Moldova through the prism of methodological constructivism. The author distinguishes such types of nationalism as a nationalism of minorities. the new nationalism of nationalizing State and the nationalism of external national homelands to which minorities belong, or may consider themselves as belonging on cultural foundations, as well as nationalism immigrants. The author demostates their interweaving and interaction, as well as a position in the political process of the country.